2022
DOI: 10.1101/2022.02.13.22270894
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tau Imaging with 18F-MK6240 across the Alzheimer’s Disease spectrum

Abstract: Tau deposition plays a critical role over cognition and neurodegeneration in Alzheimers disease (AD). Recent generation tracers have high target to background ratios giving a wide dynamic range that may improve sensitivity for detection of low levels of tau (Pascoal, Shin et al. 2018). Building on previous evidence, this study aims to characterize the effects of tau deposition as assessed by 18F-MK6240, in a large cohort of patients across the AD disease spectrum. A total of 464 participants, enrolled in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…Previous cross-sectional studies have already shown that indices of tau load made using [ 18 F]MK6240 are amenable to simplified tissue ratio methods using data acquired 90-110 minutes post-injection( 4,7 ). However, questions remain regarding the suitability of the reference region for longitudinal tracer quantification due to the bias often inherent to SUVR data( 10,11 ). This is of paramount importance because [ 18 F]MK6240 has been used in clinical trial settings to capture longitudinal changes in tau tangle pathology( 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous cross-sectional studies have already shown that indices of tau load made using [ 18 F]MK6240 are amenable to simplified tissue ratio methods using data acquired 90-110 minutes post-injection( 4,7 ). However, questions remain regarding the suitability of the reference region for longitudinal tracer quantification due to the bias often inherent to SUVR data( 10,11 ). This is of paramount importance because [ 18 F]MK6240 has been used in clinical trial settings to capture longitudinal changes in tau tangle pathology( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in post-mortem data, the tracer does not seem to bind to tau aggregates in non-AD tauopathies (5,8), except in rare frontotemporal dementia mutations associated with brain deposition of NFT (9). [ 18 F]MK6240 allows for the differentiation between cognitively unimpaired (CU), mild cognitive impairment (MCI), and AD subjects (4,10).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the brains of Alzheimer's patients, hyperphosphorylated tau causes tubulin polymerization capacity loss and configuration changes [21][22], As a result, microtubule function is disrupted [23]. Tau-tau interactions and polymerization result in insoluble PHFs and straight filaments (SFs), which form intraneuronal fibrillar deposits known as NFTs [24]. NFTs promote cell dysfunction by reducing the number of synapses, causing neurotoxicity [25].…”
Section: Tau Hyperphosphorylation Hypothesismentioning
confidence: 99%